2020
DOI: 10.1002/admt.202000271
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells with All‐Inkjet‐Printed Absorber and Charge Transport Layers

Abstract: One of the key challenges of perovskite photovoltaics is the scalable fabrication of high‐efficiency perovskite solar cells (PSCs). Not only the scalable deposition of high‐quality perovskite thin‐films itself, but also the adjacent charge extraction layers is pivotal. In this work, PSCs based on all‐inkjet‐printed absorber and extraction layers are presented, allowing for a scalable and material‐efficient deposition. The inkjet‐printed PSCs are of p–i–n‐architecture with a precursor‐based nickel oxide hole‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 102 publications
(170 reference statements)
0
72
0
Order By: Relevance
“…For the printable solar cells, various photoactive materials have been implemented in the literature including hybrid organic-inorganic materials like perovskites and organic conjugated polymer blends such as poly(3-hexylthiophene) (P3HT) (as being donor) and [6,6]-phenyl C61-butyric acid methylester (PCBM) (as being acceptor) [111][112][113][114]. Lab-scale investigations showed that printed perovskite solar cells can reach up to PCE values comparable with those of silicon solar cells, e.g., 16.6% PCE by Zhang et al [115], 17.2% PCE by Schackmar et al [116], 17.74% PCE by Li et al [117], stabilized PCE of 18.5% PCE by Eggers et al [118] and 19.6% by Li et al [119]. In addition to these developments, the printed organic cells developed by Liu et al [120] achieved 15% PCE.…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
“…For the printable solar cells, various photoactive materials have been implemented in the literature including hybrid organic-inorganic materials like perovskites and organic conjugated polymer blends such as poly(3-hexylthiophene) (P3HT) (as being donor) and [6,6]-phenyl C61-butyric acid methylester (PCBM) (as being acceptor) [111][112][113][114]. Lab-scale investigations showed that printed perovskite solar cells can reach up to PCE values comparable with those of silicon solar cells, e.g., 16.6% PCE by Zhang et al [115], 17.2% PCE by Schackmar et al [116], 17.74% PCE by Li et al [117], stabilized PCE of 18.5% PCE by Eggers et al [118] and 19.6% by Li et al [119]. In addition to these developments, the printed organic cells developed by Liu et al [120] achieved 15% PCE.…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
“…Especially vacuum drying was established for inkjet-printed layers and it is the most common protocol to produce highly efficient solar cells by crystallizing the wet film at a pressure between 10 À2 and 10 2 mbar. [12][13][14][15] Based on this effort, power conversion efficiencies (PCE) of close to 20% for partially printed devices, 15,16 and more than 17% for fully inkjet-printed solar cells, have been achieved up till now. 14 Furthermore, vacuum drying has been successfully used for other scalable methods, such as blade-coating, 17,18 spray-coating, 19 as well as for spin-coated films.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Based on this effort, power conversion efficiencies (PCE) of close to 20% for partially printed devices, 15,16 and more than 17% for fully inkjet-printed solar cells, have been achieved up till now. 14 Furthermore, vacuum drying has been successfully used for other scalable methods, such as blade-coating, 17,18 spray-coating, 19 as well as for spin-coated films. 10,20 Regardless of these successes, a detailed review of the formation of MHPs with the vacuum drying process has been lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the conventional spin coating method, typically used for small cell fabrication has its challenges when applied for large-area (>1 cm 2 ) fabrication, such as poor uniformity, solution wastage, low throughput. To overcome these limitations, various techniques have been developed, including slotdie coating [13][14][15][16][17][18], spray coating [19][20][21][22], inkjet printing [23,24], blade coating [25][26][27][28]. However, technical problems, e.g.…”
Section: Introductionmentioning
confidence: 99%